The Effect of Nicotiana glauca Leaf Extract on the Liver and Lung of Female Albino Mice: Physiological and Histopathological Studies - Omar, Salmin; Mohamed, Abdalla I.; Omar, Fatima; Alwerfali, Soad (Al-Mukhtar Journal of Sciences, 2020)
Tobacco Nicotiana glauca is a member of the Solanaceae family, found in tropical and subtropical countries especially South America, Cuba, and Brazil, as well as in North Africa, Egypt, and Libya. N. glauca is known to be a highly toxic plant. The major alkaloids are anabasine and nicotine. This study was aimed to determine the proper effects of a sublethal dose of the plant on female albino mice, as well as certain histological and physiological parameters. The three sublethal concentrations, 0.25, 0.50, and 2.8 mg/kg of the water extract were tested through oral route on female mice for determination of effects such as body weight, liver and lung weight and histology, blood parameters, and blood chemistry. The results showed that reduced body weight was slightly evident in treated females. Percent decrease of liver weight/body weight and increase lung weight/body weight have reported in 2.8 mg/kg treated female mice compared to control mice. Histology of liver and lung revealed an early sign of cell damage and accumulation of cell necrosis in both the liver and lungs. The blood parameters and blood chemistry did not reveal a significant difference between control and N. glauca treated female mice.